Global Perspectives on Sustainable Forest Management 2012
DOI: 10.5772/33619
|View full text |Cite
|
Sign up to set email alerts
|

Economic Feasibility of an Eucalyptus Agroforestry System in Brazil

Abstract: Tree varieties can include recent reforestation pastures, lumber grade trees, fruit trees, forage trees, windbreaks, pastureland, shade trees, and trees to provide conservation and soil improvement in pastures (Santos, 1990).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…This result is in accordance with the work of Bramucci [26], Dias et al [27], Rezende and Oliveira [28], Soares [29], Souza et al [21], Souza et al [24] and Wilcken et al [30], where the eucalyptus cut occurs on average between seven and 12 years.…”
Section: Cash Flowsupporting
confidence: 92%
See 2 more Smart Citations
“…This result is in accordance with the work of Bramucci [26], Dias et al [27], Rezende and Oliveira [28], Soares [29], Souza et al [21], Souza et al [24] and Wilcken et al [30], where the eucalyptus cut occurs on average between seven and 12 years.…”
Section: Cash Flowsupporting
confidence: 92%
“…Thus, to calculate the NPV and ANPV, make possible the determination of the eucalyptus cutting year, as well as the scenario that presented higher profitability (Table 6). As in studies by Souza et al [24], Arco-Verde [25] and Bramucci [23], in the first three years of production, the annual balance is negative, showing that costs are higher than revenues. From the 4th year onwards, there is a positive cash flow.…”
Section: Cash Flowsupporting
confidence: 55%
See 1 more Smart Citation
“…Besides, this tree grows well on extinct sites in public forest areas and village forest areas for fuelwood and agroforestry intendeds. Eucalyptus tree species showed a positive net return in agroforestry practices where other crop species revealed a more return than the monocropping systems (De Souza et al, 2012). Several findings were achieved on the overall productivity analysis of jackfruit, pineapple, lemon and banana-based agroforestry (Hasan et al, 2008;Kibria and Saha, 2011), mango based agroforestry (Rana, 2017), lemon based agroforestry (Raihan, 2018), akashmoni, jackfruit and litchi based agroforestry (Akter et al, 2020) systems practiced in private or participatory programs in the Madhupur tract revealed that the agroforestry practice to be beneficial in terms of benefitcost ratio analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Pinto & Rodigheri (2001) studied the mixed planting of tree species in southern Brazil and reported positive wood volume, tree survival, height and diameter at breast height (DBH) results of four Brazilian species: Libidibia ferrea, Handroanthus impetiginosus, Handroanthus albus and Peltophorum dubium. Souza et al (2012) also demonstrated a profitable system composed of clones of the natural hybrid of Eucalyptus urophylla x Eucalyptus camaldulensis and livestock fed with Urochloa. Lana et al (2016) studied the influence of Zeyheria tuberculosa (native) and Eucalyptus grandis (exotic) trees on soil fertility in a silvopastoral system that had been established for decades in the Brazilian savannah biome and concluded that E. grandis plantations accounted for most of the litter composition in this silvopastoral system.…”
Section: Introductionmentioning
confidence: 99%